2016
DOI: 10.1039/c6ra02933g
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite coatings based on copper and the products of polyethylene destruction, features of their formation, structure and antibacterial properties

Abstract: A new method of forming coatings containing copper nanoparticles and the products of polyethylene thermal destruction is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These polymer-based nanocomposites can serve as antibacterial, bacteriostatic, antifouling, and self-cleaning surfaces [ 12 , 13 , 14 ]. Copper and copper oxide NPs are very potent in water disinfection applications [ 15 ], since they exhibit high antibacterial, antifungal and antiviral properties [ 14 , 16 , 17 , 18 ]. Previous studies showed that the antibacterial activity of nanosized Cu, Cu 2 O, and CuO depends on the morphology and size of these NPs, as well as on the dissolution ability of copper species in the surrounding media [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These polymer-based nanocomposites can serve as antibacterial, bacteriostatic, antifouling, and self-cleaning surfaces [ 12 , 13 , 14 ]. Copper and copper oxide NPs are very potent in water disinfection applications [ 15 ], since they exhibit high antibacterial, antifungal and antiviral properties [ 14 , 16 , 17 , 18 ]. Previous studies showed that the antibacterial activity of nanosized Cu, Cu 2 O, and CuO depends on the morphology and size of these NPs, as well as on the dissolution ability of copper species in the surrounding media [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam dispersion is conducive to uniform films of high purity and density. Evaporating the materials under vacuum can help to avoid the contamination and oxidation of the prepared materials [11], which also allows the formation of thin antibacterial layers with prolonged release of the drug component [12,13]. Under the conditions of multi-turn evaporation deposition, multilayer composite materials or gradient structural materials with various compositions are obtained by controlling the deposition process parameters to meet the design requirements of the materials [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Therefore, comprehensive strategies are required to control and eliminate the cyanobacteriablooms. [9] Numerous efforts including direct chemical methods based on the use of algaecides, [10] flocculants or coagulants, [11] and physicala pproaches such as oxidativet echniques (eg. ozonation), [12] ultrasound technologies [13] have been developed to remove or inhibit the cyanobacteria in water.A mong the methods applied,t he direct chemical methods using chemical compounds (algaecides, flocculants or coagulants) is the most widely used effective method because of the ease of operation and relatively low costs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts including direct chemical methods based on the use of algaecides, flocculants or coagulants, and physical approaches such as oxidative techniques (eg. ozonation), ultrasound technologies have been developed to remove or inhibit the cyanobacteria in water.…”
Section: Introductionmentioning
confidence: 99%